Identifying factors that influence the use of information system applications: Study at BAZNAS throughout East Kalimantan - Lastari, Hilda; Widana, Gusti Oka (ITB AAS INDONESIA Surakarta, 2024)
SIMBA is a web-based application that is currently being updated with technological advances that have been adjusted to the needs of Amil Zakat institutions nationally. SIMBA can present financial statements that comply with Zakat accounting standards (PSAK 109). However, SIMBA has yet to be used optimally to present financial statements. This study aims to analyse the factors that influence users to use SIMBA. The research was conducted at BAZNAS in East Kalimantan using TAM, which was extended with the SEM-PLS equation model with the SmartPLS v.4 programme. Data was taken from as many as 48 respondents through questionnaires distributed online. This research wants to emphasize the importance of the habit and system quality factors. Although the habit factor is individual in nature, organizations can still intervene, for example through training and improving the quality of human resources to be able to implement the application. Meanwhile, System Quality is because the SIMBA system is basically Top Down, so BAZNAS cannot do anything and only accepts it.